Work Involvement and Organizational Commitment: Impact on Employee Performance at Telkomsel Ambon–Passo Branch - Novalien Carolina Lewaherilla (Sean Institute, 2026)
This study aims to analyze the influence of work engagement and organizational commitment on employee performance at Telkomsel Ambon-Passo Branch. The study used a quantitative approach with a survey method. The research sample consisted of 52 employees selected using a saturated sampling technique. Data collection was conducted through questionnaires, while data analysis used multiple linear regression with the help of the SPSS program. The results of the study indicate that work engagement has a positive and significant effect on employee performance. In addition, organizational commitment also has a positive and significant effect on employee performance. These findings indicate that the higher the level of work engagement and organizational commitment of employees, the better the resulting performance. This study provides implications for companies to improve work engagement and organizational commitment through human resource development, effective organizational communication, reward provision, and career development.